2021
DOI: 10.1007/s40843-020-1583-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-level-designed copper atoms on hierarchically porous gold architectures for high-efficiency electrochemical CO2 reduction

Abstract: Electrochemical CO 2 reduction is a promising technology for solving the CO 2 emission problems and producing value-added products. Here, we report a hierarchically porous Cu 1 Au single-atom alloy (SAA) as an efficient electrocatalyst for CO 2 reduction. Benefiting from the hierarchically porous architectures with abundant vacancies as well as three-dimensional accessible active sites, the as-prepared nanoporous Cu 1 Au SAA catalyst shows remarkable CO 2 reduction performance with nearly 100% CO Faraday effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…Cu-based materials are promising electrocatalysts in CO 2 RR [57][58][59]. To investigate the CO 2 RR performance of helical CuTCPP, H-CuTCPP@Cu(OH) 2 , nH-CuTCPP-Cu(OH) 2 , and Cu(OH) 2 nanoarrays were investigated using a three-electrode system.…”
Section: Co 2 Rr Performancementioning
confidence: 99%
“…Cu-based materials are promising electrocatalysts in CO 2 RR [57][58][59]. To investigate the CO 2 RR performance of helical CuTCPP, H-CuTCPP@Cu(OH) 2 , nH-CuTCPP-Cu(OH) 2 , and Cu(OH) 2 nanoarrays were investigated using a three-electrode system.…”
Section: Co 2 Rr Performancementioning
confidence: 99%
“…The catalytic current usually depends on the surface structure of NPGs and local environments during the CO 2 ER, which are normally considered from thermodynamic and kinetic aspects. On one hand, the detailed structures of NPG in previous investigation include pore size, [15,16,41] crystalline facets, [32,42,43] ECSA, [46] and atomic doping [44,45] for various electrochemical catalysis. On the other hand, physical and chemical environments also affect catalytic activity from the viewpoint of local pH value, temperature, reactant/product concentration, and mass transport of different species.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Tan et al reported a hierarchically porous Cu 1 Au SAAs as a highly efficient catalyst for CO 2 electroreduction. 65 Beneting from the hierarchically porous architectures with abundant vacancy defects, the as-prepared nanoporous Cu 1 Au SAAs catalyst shows remarkable CO 2 RR activity with nearly 100% CO Faraday efficiency in a wide potential range (À0.4 to À0.9 V vs. RHE) (Fig. 11i).…”
Section: Synergistic Single-atomic Catalysis In the Co 2 Rrmentioning
confidence: 98%
“…Another commonly used method for the synthesis of SAAs is selective dealloying, which can stabilize isolated metal atoms on the surface of another host metal. For instance, Tan et al proposed a facile route to prepare atomic Cu dispersed on hierarchically nanoporous gold architectures (denoted as np-Cu 1 Au SAAs) through a dealloying method, 65 and the fabrication process is illustrated in Fig. 6a.…”
Section: Single-atomic Alloys (Saas)mentioning
confidence: 99%